Gold mineralization in archaean cherts and iron-formations a review of the economic geology - Bellamy, R E S (Rhodes University, Faculty of Science, Department of Geology, 1979)
The distribution of gold in igneous rocks and minerals is described and discussed. Not all the gold in igneous rocks is contained within early formed crystal lattices. Evidence that gold can be associated with late stage crystallizing phases is described. It is concluded that some of the gold in hydrothermal and volcanogenic deposits may have come from a primary magmatic source rather than having been leached from solid country rock. Gold is probably transported as chloride complexes at temperatures greater than about 300Â°C. At lower temperatures it is probably transported with other metals as sulphide and thio-sulphide complexes. The precipitation of gold from the transporting medium is brought about by changes in the physico-chemical conditions within that medium. Decrease in pressure is probably not a major cause of precipitation in volcanogenic environments. The geology of volcanogenic iron-formations is described and discussed, relative to the development of greenstone belts. Oxide facies iron-formations were formed in shallow oxidizing environments. They are associated with volcanogenic and clastic sediments. Sulphide facies iron-formations were precipitated in the deeper parts of geosynclinal structures. They are associated with mafic and ultramafic rocks similar to modern oceanic volcanic assemblages. Carbonate facies iron-formations were deposited in the regions between oxide facies and sulphide facies. Other banded iron-formations are found associated with base metal massive sulphide deposits related to arctype volcanic centres. These deposits are found in the regions where carbonate facies iron-formations were formed. Exploration for and exploitation of gold deposits in Archaean iron-formations are discussed. Geochemical exploration programmes are aided by the association of gold with trace amounts of base metals. Geophysical exploration methods that can be employed include magnetometer, I.P. and E.M. surveys. The metallurgical treatment of the ores should include "roasting" because a large proportion of the gold occurs as submicroscopic grains within sulphide mineral crystals.
Keywords: Gold ores -- Geology -- South Africa; Gold mines and mining -- South Africa; Greenstone belts -- South Africa